Economic Resilience and High-Profitability of Independent Medium-Scale Oil Palm Smallholders: A Multi-Dimensional Feasibility Study in Indonesia - Kumalasari, Dwi Apriyanti; Khusniyah; Susanto, Anton; Muis, Zeni Zaenal; Putra, Demmy Filsafa Ratna (HABITAT, 2026)
Purpose: This study evaluates the financial feasibility and economic resilience of a medium-scale independent oil palm plantation in Indonesia. The research specifically examines a 17-hectare plantation to assess its potential as a sustainable and profitable farming model capable of supporting rural economic development. Design/Methodology/Approach: A quantitative descriptive approach was employed using investment feasibility analysis. The study applied several financial indicators, including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Revenue-Cost (R/C) Ratio, Benefit-Cost (B/C) Ratio, and Break-Even Point (BEP), to evaluate the plantation’s financial performance and operational efficiency. Data were analyzed to measure profitability, investment recovery, and long-term business sustainability. Findings: The results reveal that the plantation business is financially feasible and economically resilient. The NPV reached Rp 3,415,144,769, indicating substantial net benefits, while the IRR of 77% exceeded prevailing market interest rates. The R/C ratio of 2.57 demonstrates strong operational efficiency, and the payback period of 1.29 years indicates rapid investment recovery. In addition, the business achieved a break-even point at 241,562 kg of production, confirming its capacity to maintain profitability under medium-scale operations. Originality/Value/Novelty: This study highlights the strategic role of medium-scale (17-hectare) independent oil palm plantations as a balanced model between profitability and risk management. Unlike previous studies focusing mainly on smallholders or large estates, this research provides new empirical evidence regarding the economic resilience, financial sustainability, and rural development contribution of medium-scale independent plantations in Indonesia. The findings offer valuable insights for policymakers and stakeholders in strengthening the independent palm oil sector.